Atomic‐Scale Visualization and Quantification of Configurational Entropy in Relation to Thermal Conductivity: A Proof‐of‐Principle Study in t‐GeSb2Te4. Issue 8 (8th February 2021) - Chen, Yongjin; Zhang, Bin; Zhang, Yongsheng; Wu, Hong; Peng, Kunling; Yang, Hengquan; Zhang, Qing; Liu, Xiaopeng; Chai, Yisheng; Lu, Xu; Wang, Guoyu; Zhang, Ze; et al.
Abstract: It remains a daunting task to quantify the configurational entropy of a material from atom‐revolved electron microscopy images and correlate the results with the material's lattice thermal conductivity, which strides across statics, dynamics, and thermal transport of crystal lattice over orders of magnitudes in length and time. Here, a proof‐of‐principle study of atomic‐scale visualization and quantification of configurational entropy in relation to thermal conductivity in single crystalline trigonal GeSb2 Te4 (aka t ‐GeSb2 Te4 ) with native atomic site disorder is reported. A concerted effort of large t ‐GeSb2 Te4 single crystal growth, in‐lab developed analysis procedure of atomic column intensity, the visualization and quantification of configurational entropy including corresponding modulation, and thermal transport measurements enable an entropic "bottom‐up" perspective to the lattice thermal conductivity of t ‐GeSb2 Te4 . It is uncovered that the configurational entropy increases phonon scattering and reduces phonon mean free path as well as promotes anharmonicity, thereby giving rise to low lattice thermal conductivity and promising thermoelectric performance. The current study sheds lights on an atomic scale bottom‐up configurational entropy design in diverse regimes of structural and functional materials research and applications. Abstract : A proof‐of‐principle study of atomic‐scale visualization and quantification of configurational entropy in relation to thermal conductivity in single crystalline trigonal GeSb2 Te4 with native atomic site disorder is reported. The configurational entropy spontaneously intensifies phonon scattering and promotes anharmonicity, which leads to significantly reduced phonon mean free path, enabling an entropic "bottom‐up" perspective to the lattice thermal conductivity.